Copper and zinc uptake by celery plants grown on acidic soil amended with biosolids. (15th April 2016) - Haghighi, Maryam; Pessarakli, Mohammad
ABSTRACT: For trace elements, such as copper (Cu) and zinc (Zn), the bioavailability of these elements, Cu and Zn, in biosolids is important because both are essential elements and both are potential contaminants when biosolids are land applied. A greenhouse study was conducted in factorial experiment based on a completely randomized design (CRD) with four replications on a soil treated with four rates of Cu (0, 50, 100, and 150 mg/kg) and four rates of Zn (0, 150, 300, and 450 mg/kg) on celery plants to investigate the distribution and mobility of these elements as well as growth and antioxidant changes of celery. The results of antioxidant changes were inconclusive due to irregular changes with Zn and Cu applications. However, generally the results show that Cu did not affect superoxide dismutase (SOD) or peroxidase (POD) activities in most of the treatments. On the other hand, Zn stimulated SOD and POD activities in most of the treatments. The photosynthesis rate decreased with the applications of Cu and Zn at the rates above 100 and 300 mg/kg and increased in low Cu concentration (50 mg/kg) compared to S (soil without biosolid).